2017
DOI: 10.1111/ggr.12175
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Fingerprinting by Handheld Laser‐Induced Breakdown Spectroscopy

Abstract: A broad suite of geological materials was studied a using a handheld laser‐induced breakdown spectroscopy (LIBS) instrument. Because LIBS is simultaneously sensitive to all elements, the full broadband emission spectrum recorded from a single laser shot provides a ‘chemical fingerprint’ of any material – solid, liquid or gas. The distinguishing chemical characteristics of the samples analysed were identified through principal component analysis (PCA), which demonstrates how this technique for statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 83 publications
(139 reference statements)
0
29
0
Order By: Relevance
“…A cross-validation procedure was also used to ensure the robustness and performance of the classification algorithm, so that it could be used in the future as a spectral library to determine the type and geographic location of an unknown garnet specimen. In a subsequent study, Harmon et al [79] using a SciAps Z-500 handheld analyzer and a much larger sample set of 288 garnets consisting of 66 almandines, 49 andradites, 60 grossulars, 35 pyropes, 56 spessartines, and 17 uvarovites, observed that the compositional differences characterizing the six garnet compositional groups were manifest on a three-component PCA plot ( Figure 4a) and that the overall success for garnet type discrimination by PLSDA was >90% (Figure 4b). Fe-Al almandine, Mg-Al pyrope, and Mn-Al spessartine were distinguished from the other garnet groups at a success level better than 95% and Ca-Cr uvarovite at 89%.…”
Section: Garnetmentioning
confidence: 93%
See 4 more Smart Citations
“…A cross-validation procedure was also used to ensure the robustness and performance of the classification algorithm, so that it could be used in the future as a spectral library to determine the type and geographic location of an unknown garnet specimen. In a subsequent study, Harmon et al [79] using a SciAps Z-500 handheld analyzer and a much larger sample set of 288 garnets consisting of 66 almandines, 49 andradites, 60 grossulars, 35 pyropes, 56 spessartines, and 17 uvarovites, observed that the compositional differences characterizing the six garnet compositional groups were manifest on a three-component PCA plot ( Figure 4a) and that the overall success for garnet type discrimination by PLSDA was >90% (Figure 4b). Fe-Al almandine, Mg-Al pyrope, and Mn-Al spessartine were distinguished from the other garnet groups at a success level better than 95% and Ca-Cr uvarovite at 89%.…”
Section: Garnetmentioning
confidence: 93%
“…Handheld LIBS analyzers are well suited to geochemical applications [65,79,80], particularly for real-time analysis in the field. The work reported here utilized the Z-300 LIBS analyzer or its Z-500 predecessor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations